THE EFFECT OF WATCHING VIOLENT CARTOONS ON VIOLENT BEHAVIOUR: THE EFFECT OF WATCHING VIOLENT CARTOONS ON VIOLENT BEHAVIOUR - Reffita, Lea Ingne; Fatma, Inge Devita; Rahayu, Yustina (WELL BEING, 2021)
Children aged eight to nine years old are highly influenced by the violence they watch on television. In the age range of eight to nine years, the effect of television is very strong in influencing their behaviour.Method: This study is a non-experimental analytical study with a cross sectional design. The population in the study were grade III and IV male students of MI Bahrul Ulum Jombang Regency totalling 93 students, and using total sampling and analysed with the spearman rank test. Results: children who did not watch violent films were 6 people (100.0%), watching briefly as many as 70 people (100.0%), moderate category as many as 13 people (100.0%), long category as many as 3 people (100.0%) and very long category there was 1 person (100.0%). And from the results of research on violent behaviour, it is known that children who behave aggressively are 77 people (82.8%) and children who behave aggressively are 16 people (17.2%). Spearman Rank Test results obtained Sig. 0.214 is is no influence between the length of watching cartoons with violent themes on violent behaviour in third and fourth grade boys.